Extracellular anti-angiogenic proteins augment an endosomal protein trafficking pathway to reach mitochondria and execute apoptosis in HUVECs. Issue 11 (November 2018) - Chen, Mo; Qiu, Tao; Wu, Jiajie; Yang, Yang; Wright, Graham; Wu, Min; Ge, Ruowen
Abstract Classic endocytosis destinations include the recycling endosome returning to the plasma membrane or the late endosome (LE) merging with lysosomes for cargo degradation. However, the anti-angiogenic proteins angiostatin and isthmin, are endocytosed and trafficked to mitochondria (Mito) to execute apoptosis of endothelial cells. How these extracellular proteins reach mitochondria remains a mystery. Through confocal and super-resolution fluorescent microscopy, we demonstrate that angiostatin and isthmin are trafficked to mitochondria through the interaction between LE and Mito. Using purified organelles, the LE–Mito interaction is confirmed through in vitro lipid-fusion assay, as well as single vesicle total internal reflection fluorescent microscopy. LE–Mito interaction enables the transfer of not only lipids but also proteins from LE to Mito. Angiostatin and isthmin augment this endosomal protein trafficking pathway and make use of it to reach mitochondria to execute apoptosis. Cell fractionation and biochemical analysis identified that the cytosolic scaffold protein Na+/H+ exchanger regulatory factor 1 (NHERF1) associated with LE and the t-SNARE protein synaptosome-associated protein 25 kDa (SNAP25) associated with Mito form an interaction complex to facilitate LE–Mito interaction. Proximity ligation assay coupled with fluorescent microscopy showed that both NHERF1 and SNAP25 are located at the contacting face between LE and Mito. RNAi knockdown of either NHERF1 or SNAP25 suppressed not only the mitochondrial trafficking of angiostatin and isthmin but also their anti-angiogenic and pro-apoptotic functions. Hence, this study reveals a previously unrealized endosomal protein trafficking pathway from LE to Mito that allows extracellular proteins to reach mitochondria and execute apoptosis.